Improved Thermal Insulating Properties of Renewable Polyol Based Polyurethane Foams Reinforced with Chicken Feathers - Aranberri, Ibon (Polymers (Basel), 2019)
In the present work, sustainable rigid polyurethane foams (RPUF) reinforced with chicken feathers (CF) were prepared and characterized. The bio-based polyol used to formulate the foams was obtained from castor oil. This investigation reports the influence of the chicken feathers fibers as reinforcement of RPUF, on water absorption, thermal, mechanical and morphological properties (field-emission scanning electron microscope—FESEM) and thermal conductivity on water-blown biofoams. It was found that the biofoams improved thermal insulating properties when CF was added. The addition of CF to foams provided lower heat flux density to the biofoams obtaining bio-based materials with better insulation properties. The results obtained in this study proved that the incorporation of CF to RPUF modified the cell structure of the foams affecting their physical and mechanical properties, as well as functional properties such as the heat transmission factor. These biofoams containing up to 45% of bio-based materials have shown the potential to replace fully petroleum-based foams in thermal insulation applications.